Effects of composite lamina properties on fundamental Lamb wave mode dispersion characteristics. (June 2015) - Pant, S.; Laliberte, J.; Martinez, M.; Rocha, B.; Ancrum, D.
Abstract: Lamb waves are useful for detecting changes in material properties, as their propagation characteristics are sensitive to changes in the medium through which they travel. Defects and damage in materials/structures can be detected by analyzing the difference between the phase and/or group velocity amplitude and mode changes of Lamb waves' propagation in damaged versus un-damaged specimens. The propagation characteristics of Lamb waves are described in the form of dispersion curves, relating phase and/or group velocities to the product of frequency and thickness, with these curves being generated by solving the Lamb wave equations. In this article, the effect on the Lamb wave propagation/dispersion due to changes in the material properties such as E 11, E 22, G 12, and density were analyzed for three different composite laminate types – unidirectional, cross-ply, and quasi-isotropic, all constructed out of 16-plies of unidirectional carbon-fiber epoxy prepregs. The analysis was performed by obtaining the characteristic Lamb waves' phase velocity dispersion and slowness curves for each laminate type. This was done by reducing E 11, E 22, and G 12 by 5%, 10%, 15% and 30%, and density by 1%, 2%, 5% and 10% with the intent of representing manufacturing and in-service defects. Since the Lamb waves' velocity in a composite laminate varies with the propagation direction, the laminates were analyzed at 0°, 20°, 45°, 70°, and 90° propagation angles, with all the aforementioned variations. A program developed in MATLAB was used to generate the dispersion curves for the fundamental anti-symmetric and symmetric Lamb wave. The information provided in this paper can be used to select the proper Lamb wave modes, excitation frequency, which in turn governs sensor selection, data acquisition hardware, and damage detection algorithm for structural health monitoring of composite structures.